A Study on the C-E Translation Practice of Biographies of Silk Celebrities (Excerpt) from the Perspective of Catford’s Shifts Theory - Linbo Xiao; Weihua Hu (Journal of Linguistics and Communication Studies, 2023)
Nowadays, many outstanding traditional Chinese cultures have stepped onto the global stage and gained recognition from the public. Therefore, more classic works of excellent traditional Chinese culture should be introduced to foreign countries, making contributions to the diversity and inclusiveness of world culture and promoting a more harmonious global development. Chinese textile and clothing culture, especially ancient Chinese silk culture, is an important aspect of translation to the outside world. The source text for this study is selected from Chapter 2 of the book Biographies of Silk Celebrities. The excerpt mainly introduces the important deeds of several ancient Chinese silk craftsmen, highlighting the spirit of struggle of the older generation of industrialists. The book belongs to informative text, conveying true and objective information. It uses precise language, presents factual content, and is highly readable. However, the abundance of textile terminology, complex sentence structures, and differences in English and Chinese syntactic expressions have posed certain challenges to this translation task. To deal with these translation difficulties, translators need to apply transformation techniques reasonably during the translation process to improve the quality of the translation. Cartford believes that when the source language is translated into the target language, meaning equivalence can be achieved by using translation shifts, breaking away from formal correspondence. Guided by Catford’s theory, this study combines the characteristics of the original text to analyze specific cases and explore various types of shifts to achieve the translation purpose. In this study, level shift includes the conversion of noun plurals and tenses. Category shift involve structural shift, class shift, and unit shift. Structural shift is mainly used for converting prepositional phrases, passive voice, and negation expressions. Class shift is mainly used to convert verbs into nouns, adjectives, and prepositions. Unit shifts is primarily used between phrases, clauses, and sentences. Through these shifts, the translation conforms to the writing conventions of the target language, is easily accepted by readers, and helps achieve the desired translation effect.